Circadian Rhythms of Endothelial Nitric Oxide Synthase and Toll-like Receptors 2 Production in Females with Rheumatoid Arthritis Depending on NOS3 Gene Polymorphism - Zaichko, Kateryna; Zaichko, Nataliia; Maievskyi, Oleksandr; Korotkyi, Oleksandr; Falalyeyeva, Tetyana; Fagoonee, Sharmila; Pellicano, Rinaldo; Abenavoli, Ludovico; Stanislavchuk, Mykola (Reviews on Recent Clinical Trials, 2020)
Background: Rheumatoid Arthritis (RA) is an autoimmune polygenic disease characterized by rapid disability progression and high prevalence. Progression of RA is closely associated with chronobiological changes in the production of some hormones and inflammatory mediators, influencing the disease course and therapy efficacy. The main pathogenetic mechanism of RA is angiogenesis, which is controlled by biological clock-genes. Further investigation of circadian rhythms of angiogenic mediators production in RA patients may be considered as important and relevant. The aim of this study was to establish daily variability of serum endothelial Nitric Oxide Synthase (NOS3) and toll-like receptors 2 (sTLR2) levels in female RA patients depending on the NOS3 gene polymorphism. Methods: We examined 173 RA patients (100% female) aged 43.7 ± 7.35 years and 34 age-matched healthy women without joint diseases and autoimmune diseases (control). RA was diagnosed by ACR/EULAR 2010 criteria. Blood serum NOS3 and sTLR2 levels were determined at 08:00 and 20:00 using Cloud-Clone Corp kits (USA). NOS3 T-786С (rs2070744) polymorphism was determined by Real-Time PCR (Bio-Rad iCycler IQ5) using SNP-express kits. The SPSS22 software package was used for statistical processing of the results. Results: Females with RA demonstrated oppositely directed serum NOS3 and sTLR2 daily changes: NOS3 level in the morning (08:00) was lower than in the evening (+ 45.5 ± 30.7%), and sTLR2 level in the evening (at 20:00) was lower than in the morning (-21.6 ± 13.1%). RA patients had differences in NOS3 and sTLR2 production depending on NOS3 T786C genotype. CC subjects had NOS3 level at 08:00, 20:00 and day average levels lower (16-25%), and sTLR2 level higher (24-27%) than those of TT subjects. RA patients, carriers of CC genotype, had higher chances of NOS3 and sTLR2 aberrant production compared to TT and TC genotype carriers (OR = 2.99 and 4.79, respectively). Conclusion: RA patients demonstrated oppositely directed circadian changes of serum NOS3 and sTLR2. CC genotype carriers had lower NOS3 and higher sTLR2 production rates than TT and TC genotype carriers.
Keywords: endothelial nitric oxide synthase